Solve for x and y,2x-y+3=0,3x-5y+1=0
kundasolanki:
by elemination x = —1, y = 1
Answers
Answered by
2
From first eq. We get y=2x+3
Put this in other eq. As 3x-5(2x+3)+1=0
3x-10x-15+1=0
-7x-14=0
X=-2
Y=-1
Put this in other eq. As 3x-5(2x+3)+1=0
3x-10x-15+1=0
-7x-14=0
X=-2
Y=-1
Answered by
1
X=y-3/2
3x-5y+1=0
3×(((y-3)/2)-5y+1=0
3y-9-10y+2=0
7y=-7
Y=-1
x=-1-3/2
X=-4/2
X=-2
3x-5y+1=0
3×(((y-3)/2)-5y+1=0
3y-9-10y+2=0
7y=-7
Y=-1
x=-1-3/2
X=-4/2
X=-2
Similar questions
History,
9 months ago
English,
9 months ago
English,
1 year ago
India Languages,
1 year ago
History,
1 year ago